SIMULASI PERFORMANSI TCP PADA ATM DENGAN KELAS LAYANAN ABR - Z. Hutapea, Ruslan
Abstract : Transmission Control Protocol is the most used transport protocol in data network nowadays. As the demand of high speed data transmissionincreas, it is very important to study the performance of TCP over Available Bit Rate, as one of many service class in the ATM networks. TCP traffic over ABR is controlled by two flow control mechanism. In the TCP layer flow control will be done by limiting the number of segment transmitted to the network while in the ABR layer is done by adjusting cell rate transmission from source based on feedback received from the network. To see how these two flow control work, we make a simulation under some different variation of system parameter. Research on TCP over ABR usually done with uniform segment rate and segment size and without specific buffer management. In this thesis we make a modelling and simulation to evaluate performance of TCP over ABR in an ATM network. Investigation on system performance using TCP source with some different rate and segment size, buffer management, number of connections and with VBR background traffic is done. Simulation results show that system performance under some specific condition can vary depend on the TCP flow control as a dominant factor. Under another condition, ABR flow control become a dominant factor that influence system performance.